Morphological characteristics and phylogenetic analyses reveal Steccherinum farinaceum sp. nov. (Polyporales, Basidiomycota) from Yunnan Province, China - Zhang, Xiaojie; Wang, Jiayong; Yang, Rongcong; Zhang, Shihui; Zhang, Sicheng; Xu, Jin; Zhao, Changlin (Phytotaxa, 2025)
The wood-inhabiting fungi play a crucial role in wood degradation and the cycle of matter within the ecological system. They are considered the “key player” in wood decomposition because of their ability to decompose woody lignin, cellulose, and hemicellulose. Steccherinum farinaceum is described and illustrated based on morphological and molecular evidence. This species is characterized by white to cream basidiomata with farinaceous hymenophore and ellipsoid to subglobose basidiospores (4.0–5.5 × 3.5–4.5 µm). Sequences of the internal transcribed spacer region (ITS) and the large subunit nuclear ribosomal RNA gene (nLSU) from the studied samples were generated, and phylogenetic analyses were performed using Maximum Likelihood, Bayesian Inference, and Maximum Parsimony methods. The phylogenetic analysis indicated that the new species S. farinaceum is nested within the genus Steccherinum and is sister to two related species, S. wumengshanense and S. yunnanense. A description, illustrations, and phylogenetic analysis results of the new species are provided. Additionally, the new species is compared with closely related taxa.